COVID-19, Cancer, and Congregation: An Observational Study from a Tertiary Care Hospital in New Delhi - Nair, Rajesh; Kaushik, M. R.; Kishore, Kislay; Singh, H. P.; Vardhan, Vasu; Suresh, P.; Kumar, Manish; Rathore, Anvesh; Thareja, Sandeep; Rana, Sandeep; Bhuva, Dipen; Malviya, Anupam; Patel, Amol (Indian Journal of Medical and Paediatric Oncology, 2021)
Objective Indian data on cancer patients with coronavirus disease 2019 (COVID-19) infection and its outcome are limited. Infectivity and outcome among cancer patients staying in large congregations are not known. We conducted this study to address this lacuna in literature.Methods This was a retrospective–prospective, observational study of hospitalized cancer patients with proven COVID-19 infection, conducted at tertiary care hospital in New Delhi after ethical approval. We analyzed clinical, laboratorial parameters, and outcomes in these patients.Results All 32 admitted male patients became COVID-19 positive and 10 (31%) patients were symptomatic. Median age was 37.5 years (range: 16–64). Sixteen health-care workers (HCWs) were working in the cancer ward (paramedical staff: 4, nurses: 6, residents: 4, and consultants: 2). Among HCWs, two nursing staff and three paramedical staff contracted asymptomatic COVID-19. Eighteen (56%) and 14 (44%) patients were on curative and palliative treatment, respectively. Leukopenia (total leukocyte count <4,000/μL) was seen in 37.5% of cases. Grades 4, 3, 2, and 1 neutropenia were present in 12.5% of patents. Two (6.25%) patients had features of critical COVID-19. Eight (25%) patients received treatment with hydroxychloroquine + azithromycin. Five patients died. Three patients had features of progressive disease with poor performance status. One critical COVID patient survived and one succumbed to COVID-19. Patients shared a common dining room, sanitation area.Conclusion Seventy percent of cancer patients were asymptomatic. Cancer patients living in congregation areas are susceptible to COVID-19 with 3% mortality rate. Recent chemotherapy and associated cytopenias may not increase the risk in cancer patients with COVID-19 treated with curative intent. Palliative intended patients are at increased risk of death. N-95, personal protective equipment, and adherence to infection control measures should be encouraged.
Keywords: cancer; congregation; coronavirus disease 2019; outcomes; RT-PCR negativity